The Existance of Land Bengkok as a Village Asset in Relation to Sustainable Village Development - Umar Ma’ruf; Istinah, Siti Rodhiyah Dwi; Ananta, Wulan Yulia (KnE Social Sciences, 2025)
This paper aims to identify and analyze the existence of bengkok land as a village asset and a supporter of sustainable village development. The approach used in this research is juridical and sociological, namely combining legal aspects with social reality in the field. The research specifications are descriptive, and data were collected through interviews with related sources and literature studies, then analyzed qualitatively. The results of the study show that the Village Law (Law 6/2014 jo. 3/2023), Permendagri 1/2016 and Permendagri 3/2024 state that the existence of bengkok land is a village asset or is referred to as village treasury land. This is because the regulation recognizes the original rights. Bengkok land is village land allocated to the village head and his staff as a source of additional income, which can be managed and utilized for activities such as farming, fish farming, or renting but with the restriction that it cannot be sold or mortgaged without permission from the village. Proper management of bengkok land can support sustainable village development. Utilization of bengkok land for organic farming, renewable energy, or ecotourism can boost the economy. The success of bengkok land management is highly dependent on the active participation of the village community. Transparency and accountability in the management of village assets are essential to prevent misuse and ensure that the benefits are felt by all residents.